2022
DOI: 10.1007/s00170-022-10376-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface quality and cylindricity of ultrasonic elliptical vibration–assisted centerless grinding of micro-rod YAG single crystals

Abstract: Micro-rod YAG single crystals are the most commonly used laser crystals for laser gain mediums with a high power. However, brittle fracture and crack damages are easy to occur in the grinding process of micro-rod brittle crystals due to their large length-to-diameter ratio, high brittleness and high hardness. In this work, the modal, frequency and harmonic response of the transducer under ultrasonic elliptical vibration are analyzed by using nite element simulation. Then, the mechanical structure of ultrasonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the articles of Pereverzev et al (2015) and Akintseva et al (2021) studied the cutting force taking into account the dynamic properties of the machining system. The article by Hu et al (2022) showed that when processing brittle crystals, grinding efficiency can be increased by using ultrasonic elliptical vibration. The article by Li et al (2023) presented the results of molecular dynamics simulation of traditional grinding and laser grinding.…”
Section: Introductionmentioning
confidence: 99%
“…In the articles of Pereverzev et al (2015) and Akintseva et al (2021) studied the cutting force taking into account the dynamic properties of the machining system. The article by Hu et al (2022) showed that when processing brittle crystals, grinding efficiency can be increased by using ultrasonic elliptical vibration. The article by Li et al (2023) presented the results of molecular dynamics simulation of traditional grinding and laser grinding.…”
Section: Introductionmentioning
confidence: 99%